Prenatal-onset Niemann-Pick type C disease with nonimmune hydrops fetalis - Sürmeli Onay, Özge; Yakarisik, Selin; Korkmaz, Ayse; Akcoren, Zuhal; Yuce, Aysel; Runz, Heiko; Stampfer, Miriam; Yurdakok, Murat (Pediatrics and neonatology, 2013)
Niemann-Pick type C (NPC; OMIM 257219) disease is a neurodegenerative lysosomal storage disorder characterized by accumulation of unesterified cholesterol in the lysosomal/late endosomal system. This autosomal recessive disorder occurs in approximately 1/150,000 births. The broad clinical spectrum ranges from a prenatal severe presentation to an adult-onset chronic neurodegenerative disease. Data about prenatal presentation of NPC are limited. A female newborn was born at 342 weeks' gestation with a birth weight of 3070 g, and transferred to the Neonatal Intensive Care Unit because of nonimmune hydrops fetalis (NIHF) and respiratory distress. On admission, a physical examination revealed skin edema, mild respiratory distress, and abdominal distention due to massive ascites. Hepatosplenomegaly and cholestasis increased progressively and bleeding diathesis occurred. Results of an abdominal ultrasonography showed hepatosplenomegaly and segmental multicystic dysplastic left kidney. Foamy cells with a lysosomal phospholipid storage pattern compatible with NPC were found in the bone marrow smear. Cultured fibroblasts showed a strongly elevated filipin staining (classical NPC cellular phenotype), establishing the diagnosis of NPC. The infant died on the 52nd day of life because of respiratory distress due to lung involvement of NPC, massive ascites, and progressive liver failure. Results of an autopsy showed multiorgan storage disease involving the liver, spleen, lymph nodes, thymus, lungs, and brain. Here, we present a preterm infant with NIHF as a sign of severe prenatal-onset NPC and review the literature.